Abnormal Cardiac Electrophysiological Activity in the Suku Anak Dalam Living in A Malaria-Endemic Area - Ade Suryaman; Ismail Fahmi; Sarbaini Sarbaini; Elly Nurachman; Chairil Anwar; Dwi Handayani (GLOBAL HEALTH SCIENCE GROUP, 2025)
Malaria is a life-threatening parasitic disease. Although the annual incidence of the parasite has decreased, malaria continues to be a health concern. The incidence of malaria remains high in tropical regions. The Suku Anak Dalam is the indigenous population of Jambi who live in the tropical forest. With limited access to healthcare, low levels of education, poor socio-economic status, and a nomadic lifestyle, the Suku Anak Dalam are vulnerable to malaria infections. Malaria infections trigger immune responses that cause issues with capillary blood vessels and the heart. Changes in the electrocardiogram are considered indicative of cardiac problems. This study aims to understand the electrocardiogram patterns of the Suku Anak Dalam community living in malaria-endemic areas, in order to support preventive measures regarding cardiac issues in populations residing in such regions. This research employed a descriptive cross-sectional design, utilising accidental sampling of nine adult members of the Suku Anak Dalam community who reside in the forest area of Sungai Terap Jelutih village, Batin XXIV Sub-district, Batanghari Regency, Jambi Province, and who consented to undergo electrocardiogram (ECG) recording. The ECG results were subsequently analysed descriptively by a ECG specialist, and the findings were then summarised. The results of electrocardiogram recordings from nine respondents showed Left Bundle Branch Block, along with signs of anaemia and hypertension. The conclusion is that the presence of Left Bundle Branch Block may be due to malaria infection, which triggers immune disturbances resulting in capillary and cardiac complications. Continuous cardiac examinations are necessary in endemic areas as a preventive measure.